EFEKTIVITAS PENGGUNAAN QRIS SEBAGAI ALAT PEMBAYARAN NONTUNAI DENGAN PENDEKATAN TEORI TECHNOLOGY ACCEPTANCE MODEL (TAM)(Studi Kasus Masyarakat Kec. Rengat, Kab. Indragiri Hulu, Prov. Riau) - Surya Agusyahputra; Amsah Hendri Doni (Adisam Publisher, 2025)
This inquiry was prompted that there were still people in Rengat who do not know about QRIS as a non-cash payment style and some who already know about QRIS as a non-cash payment style but have not used it because it is more convenient to use cash than non-cash money. The purpose of this study was to investigate the effectiveness of adopting QRIS as a non-cash payment style among the people of Rengat (millennial generation) and how much effectiveness of using QRIS as a non-cash payment style is among the people of Rengat (millennial generation). This form of examination employs quantitative research with a descriptive method, this inquiry was done in the Rengat community. The population in this study was the young adult in the Rengat community 20 to 40 years totaling 17,450 people. The sample was drawn from non-probability samples, and there were 99 people in all. The evidence gathering technique employed in this study was a poll. The data analysis method used in this investigation is descriptive effectiveness analysis, which is carried out while performing calculations exactly in accordance with the formula by accumulating the total points of the respondent's response results received in portions while accumulating the ideal score and then multiplying by 100%. Furthermore, the score obtained will be converted through the effectiveness measurement standard. The studys findings denote that adopting QRIS as a non-cash payment instrument in the Rengat community (millennial generation) is quite high. This is supported by the data collecting findings acquired from the data analysis procedure, where the value of each indicator is 84.12%, indicating a very high degree of effectiveness based on the effectiveness assessment criteria.